Tourism Management : an introduction - Page, Stephen J. (Oxford, UK : Elsevier / Butterworth-Heunemann, 2011)
Offers an introduction to the fundamentals of tourism. This title traces the evolution and future development of tourism and the challenges facing tourism managers in this growing sector of the world economy. It is illustrated with diagrams and colour images, and contains short case studies, as well as data and statistics
Includes index.
Keywords: Tourism management; Hospitality industry -- Management